Workspace Analysis and Trajectory Planning of the Main Manipulator for Virtual Laparoscopic Surgery - Jinxing Qu (Jixie chuandong)
As a bridge between manual operation and virtual surgical scene， the main manipulator can reproduce various laparoscopic surgical actions and plays an important role in the virtual surgical system. A main manipulator with a passive series connection structure is designed to suit the application requirements of the virtual laparoscopic surgery system. The forward kinematics model of main manipulator is obtained through kinematics operation， the main manipulator workspace and trajectory planning analysis is conducted in the Matlab software. Both qualitative and quantitative analysis of the kinematic performance of the main manipulator is carried out based on the location information collected by 3D electromagnetic tracking system. The results show that， the parameter design of the main manipulator is rational， the kinematics model of the main manipulator is correct， and the workspace analysis and the trajectory planning meet the needs of the virtual laparoscopic surgery， which lay the foundation for the virtual laparoscopic surgery system as well as the motion control and pre-operation plan of the main manipulator.